Repeated Influenza Vaccination Boosts and Maintains H1N1pdm09 Neuraminidase Antibody Titers - Hansen, Lena; Zhou, Fan; Amdam, Håkon; Trieu, Mai-Chi; Cox, Rebecca Jane (Frontiers in Immunology, 2021)
Antibodies to influenza surface protein neuraminidase (NA) have been found to reduce disease severity and may be an independent correlate of protection. Despite this, current influenza vaccines have no regulatory requirements for the quality or quantity of the NA antigen and are not optimized for induction of NA-specific antibodies. Here we investigate the induction and durability of NA-specific antibody titers after pandemic AS03-adjuvanted monovalent H1N1 vaccination and subsequent annual vaccination in health care workers in a five-year longitudinal study. NA-specific antibodies were measured by endpoint ELISA and functional antibodies measured by enzyme linked lectin assay (ELLA) and plaque reduction assay. We found robust induction of NA inhibition (NAI) titers with a 53% seroconversion rate (>4-fold) after pandemic vaccination in 2009. Furthermore, the endpoint and NAI geometric mean titers persisted above pre-vaccination levels up to five years after vaccination in HCWs that only received the pandemic vaccine, which demonstrates considerable durability. Vaccination with non-adjuvanted trivalent influenza vaccines (TIV) in subsequent influenza seasons 2010/2011 – 2013/2014 further boosted NA-specific antibody responses. We found that each subsequent vaccination increased durable endpoint titers and contributed to maintaining the durability of functional antibody titers. Although the trivalent influenza vaccines boosted NA-specific antibodies, the magnitude of fold-increase at day 21 declined with repeated vaccination, particularly for functional antibody titers. High levels of pre-existing antibodies were associated with lower fold-induction in repeatedly vaccinated HCWs. In summary, our results show that durable NA-specific antibody responses can be induced by an adjuvanted influenza vaccine, which can be maintained and further boosted by TIVs. Although NA-specific antibody responses are boosted by annual influenza vaccines, high pre-existing titers may negatively affect the magnitude of fold-increase in repeatedly vaccinated individuals. Our results support continued development and standardization of the NA antigen to supplement current influenza vaccines and reduce the burden of morbidity and mortality.